1974
DOI: 10.1161/01.res.35.6.835
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of Adrenergic Alpha and Beta Receptors Mediating the Vasomotor Responses of Cerebral Arteries Ir Vitro

Abstract: The adrenergic receptors in the isolated feline middle cerebral artery were characterized pharmacologically using a sensitive system for recording circular contractions in vitro. Epinephrine, norepinephrine, isoproterenol. and phenylephrine contracted the vessel in the mentioned order of potency. Together with the inhibitory patterns obtained with graded doses of piperoxan (reversible competitive inhibition) and dibenamine or phenoxybenzamine (irreversible competitive inhibition), these results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
2

Year Published

1980
1980
2004
2004

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(96 citation statements)
references
References 18 publications
6
88
2
Order By: Relevance
“…In vitro application of catechol amines to pial vessels generally produces contrac tion (Kuschinsky and Wahl, 1975;Edvinsson et ai., 1976). Some authors have found biphasic dose-re sponse curves (Duckles and Bevan, 1976) to adren ergic agonists, and the low potency of norepineph rine and phenylephrine has led some investigators to suggest that a-receptors are different from those found in peripheral arteries (Edvinsson and Owman, 1974). Responses to intravascular cate cholamines have been less well studied in the brain, but studies with peripheral vessels have suggested the presence of endothelial a2-adrenoreceptors (Langer et ai., 1980;McGrath, 1982) and that these mediate relaxation (Cocks and Angus, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro application of catechol amines to pial vessels generally produces contrac tion (Kuschinsky and Wahl, 1975;Edvinsson et ai., 1976). Some authors have found biphasic dose-re sponse curves (Duckles and Bevan, 1976) to adren ergic agonists, and the low potency of norepineph rine and phenylephrine has led some investigators to suggest that a-receptors are different from those found in peripheral arteries (Edvinsson and Owman, 1974). Responses to intravascular cate cholamines have been less well studied in the brain, but studies with peripheral vessels have suggested the presence of endothelial a2-adrenoreceptors (Langer et ai., 1980;McGrath, 1982) and that these mediate relaxation (Cocks and Angus, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous findings in several spe cies (Duckles and Bevan, 1976;Lee et al, 1981), the NE contractile dose-response curves in cerebral arteries of the dog and cat were composed of two phases: an initial phase of smaller contractions in duced by NE in concentrations from 10 -6 to 3 X 10-4 M, followed by a second phase of sharply el evated contractile responses induced by higher con centrations ofNE 00-3 -3 x 10-3 M) ( sponses may be mediated by non-u-adrenergic receptors (Edvinsson and Owman, 1974;Bevan, 1981), the effect of bilirubin on the initial phase of NE dose-response curves was examined. In the presence of bilirubin (3 x 10-5 M), NE-induced contractions were usually similar to or smaller than the contractions induced before addition of bilirubin (Fig.…”
Section: Effects Of Bilirubin On Vasoconstriction Induced By Nementioning
confidence: 99%
“…When the contraction is blocked by alpha adrenergic antagonists, isoproterenol induces relaxation, in a dose dependent manner in human, 1 -4 cat, 3 and dog 4 cerebral arteries. This relaxation was blocked by propranolol.…”
mentioning
confidence: 99%